2003
DOI: 10.1128/aac.47.6.1912-1921.2003
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin and Alpha Interferon Enhance Death Receptor-Mediated Apoptosis and Caspase Activation in Human Hepatoma Cells

Abstract: The molecular mechanisms underlying the clinical effects of alpha interferon (IFN) and ribavirin are not understood. Elimination of infected cells occurs in part by cytotoxic T lymphocytes (CTLs) expressing CD95 ligand and thereby attacking target cells which are positive for the death receptor CD95. Since many viruses have evolved mechanisms to inhibit apoptosis, the opposite, namely, promotion of apoptosis, could be a strategy to strengthen the host antiviral response. In the present study, we have asked whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…Although there were mixed effects, caspase 8, the main activator of the Fas-mediated apoptosis pathway, was up-regulated in ribavirin-treated patients. This is in keeping with a previous report from Schlosser et al, 30 who showed that IFN and ribavirin treatment of Hep G2 cells resulted in increased caspase 8 expression and increased Fas-mediated apoptosis. The finding that apoptotic pathways are also up-regulated in responders to therapy suggests that apoptosis may be a critical component of the response to HCV treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Although there were mixed effects, caspase 8, the main activator of the Fas-mediated apoptosis pathway, was up-regulated in ribavirin-treated patients. This is in keeping with a previous report from Schlosser et al, 30 who showed that IFN and ribavirin treatment of Hep G2 cells resulted in increased caspase 8 expression and increased Fas-mediated apoptosis. The finding that apoptotic pathways are also up-regulated in responders to therapy suggests that apoptosis may be a critical component of the response to HCV treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Other investigators have observed that during apoptosis, chromatin condensation occurs, which results in reduced PI fluorescence (O'Brien et al, 1998). It has now become an acceptable practice to take advantage of the reduced PI fluorescence due to chromatin compaction to quantify apoptosis by observing the presence of hypodiploid nuclei using flow cytometry (Hess et al, 2001;Schlosser et al, 2003;Souza-Fagundes et al, 2003).…”
mentioning
confidence: 99%
“…IFN binds to its cell surface receptor leading to the expression of a set of proteins that mediate the biological actions of IFN. The process is regulated by Janus kinases (JAK) and signal-transducing and activating factors of transcription (STAT) [47], thereby either affecting directly infected or uninfected cells or interfering indirectly with the regulation of the immune system [46]. In cells infected with RNA viruses, IFN induces the double-stranded RNA-dependent serine/ threonine protein kinase PKR, a key molecule with respect to the antiviral potency of IFN [46].…”
Section: Therapeutic Apoptotic Strategiesmentioning
confidence: 99%
“…The process is regulated by Janus kinases (JAK) and signal-transducing and activating factors of transcription (STAT) [47], thereby either affecting directly infected or uninfected cells or interfering indirectly with the regulation of the immune system [46]. In cells infected with RNA viruses, IFN induces the double-stranded RNA-dependent serine/ threonine protein kinase PKR, a key molecule with respect to the antiviral potency of IFN [46]. Apart from this direct antiviral potency, cells overexpressing PKR are more sensitive to apoptosis, and it has been demonstrated that PKR can induce PARP cleavage and an upregulation of CD95 mRNA in NIH 3T3 cells [46].…”
Section: Therapeutic Apoptotic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation